2018
DOI: 10.1097/scs.0000000000004672
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Cone-Beam Computed Tomography for Evaluating Bone Density and Cortical Bone Thickness at the Implant Site: Micro-Computed Tomography and Histologic Analysis

Abstract: The aim of this study was to evaluate the accuracy of cone-beam computed tomography (CBCT) for determining cortical thickness and the gray value, investigating its correlation with micro-computed tomography (CT) and histology analysis. Sixty-two bone samples from 4 anatomic regions of the jaw were analyzed. A radiographic surgical stent was used during CBCT and bone sample harvesting. The cortical thickness and gray value of the planned implant were evaluated by CBCT. Bone volumetric fractions, bone mineral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
0
25
0
3
Order By: Relevance
“…The capabilities of clinical CT to characterize structural properties of human skeletons have been explored. Predicting cortical bone densities and thickness by cortical shells of the ROIs using clinical CT provided excellent correlations with micro CT results 29,30 . The accuracy of bone densities calculated from Hounsfield units (HUs) from CT data has been demonstrated 31 , and three-dimensionally (3D) reconstructed axial CT images could accurately define the border of the cortical bone 32,33 .…”
mentioning
confidence: 81%
“…The capabilities of clinical CT to characterize structural properties of human skeletons have been explored. Predicting cortical bone densities and thickness by cortical shells of the ROIs using clinical CT provided excellent correlations with micro CT results 29,30 . The accuracy of bone densities calculated from Hounsfield units (HUs) from CT data has been demonstrated 31 , and three-dimensionally (3D) reconstructed axial CT images could accurately define the border of the cortical bone 32,33 .…”
mentioning
confidence: 81%
“…Consequently several comparative studies assessing the image performance of the CBCT devices with micro-CT as a possible tool of validation [11,13,[15][16][17][18][19][20]45]. Considering our results, the measured 38.71 µm mean spatial resolution of the micro-CT images provides micromorphologically reliable images, since the spatial resolution is smaller, than the scanned human anatomical structure such as human cancellous bone, in which the trabeculae have a dimension of 50 -300 µm [16,46].…”
Section: Discussionmentioning
confidence: 68%
“…Numerous publications have been investigated the use of cone beam computed tomography (CBCT) for evaluating small anatomical structures in dentistry e.g. root canal morphology in endodontics [1][2][3][4][5][6][7][8][9][10] or bone quality assessment in maxillofacial surgery [11][12][13][14][15][16][17][18][19][20]. It is essential to visualize these details to set up the proper diagnosis and treatment plan, hence clinicians need to select the adequate imaging technique with the appropriate resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Rashad et al 13 standardised the bone samples temperatures previous perforation and showed that prolonged time of osteotomies with the tips of the ultrasonic system is associated with higher bone temperatures when compared with conventional drilling. In this study, we use bone samples with equal temperatures with a mean cortical bone thickness of 0.78 mm, bone mineral density of 1.10 g/cm 3 and standardised morphometric parameters to simulate a mandibular bone body, without variations in the bone quality of the different groups studied 16 . Anyway, the reached temperatures for the ultrasonic preparation implant site can be as equally safe as the drilling conventional rotatory system, since it is necessary to reach at least 47°C for 60 s for significant bone damage, 3,17 and, in our study, we reached a maximum mean perforation of 34.4°C and 79 s.…”
Section: Discussionmentioning
confidence: 99%